2017
DOI: 10.1021/acschembio.7b00456
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reconstitution of OxyA Enzymatic Activity Clarifies Late Steps in Vancomycin Biosynthesis

Abstract: Studies on the biosynthesis of glycopeptide antibiotics have provided many insights into the strategies that Nature employs to build architecturally strained molecules. A key structural feature of vancomycin, the founding member of this class, is a set of three aromatic cross-links that are introduced via yet unknown mechanisms. Previous reports have identified three cytochrome P450 enzymes involved in this process and demonstrated enzymatic activity for OxyB, which installs the first aromatic cross-link. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…Reaction monitoring was performed every 30 minutes using LC/MS, with purification performed by preparative RP-HPLC after completion of the reaction (1-2 hours). Whilst our study was ongoing a report of GPA peptide synthesis using a hydrazide method was reported; 29 however, this peptide contained a non-standard, racemisation-resistant tyrosine residue at the peptide C-terminus.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Reaction monitoring was performed every 30 minutes using LC/MS, with purification performed by preparative RP-HPLC after completion of the reaction (1-2 hours). Whilst our study was ongoing a report of GPA peptide synthesis using a hydrazide method was reported; 29 however, this peptide contained a non-standard, racemisation-resistant tyrosine residue at the peptide C-terminus.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…[3,4] The biosynthesis of these crosslinks has been an active area of research for over 20 years.P ioneering in this regard were early results from genetic studies,which suggested that three cytochrome P450 enzymes-OxyB,OxyA, and OxyC-install the synthetically challenging aromatic linkages in that order ( Figure 1a). [8][9][10] Similar studies have been extended to teicoplanin and complestatin. [8][9][10] Similar studies have been extended to teicoplanin and complestatin.…”
mentioning
confidence: 86%
“…[10] To assess whether the product of OxyA would serve as as ubstrate for OxyC,w eb egan by cloning the corresponding gene from A. orientalis and expressing it as ahexa-His fusion construct in E. coli (Figure 1b,T able S1 in the Supporting Information). [10] To assess whether the product of OxyA would serve as as ubstrate for OxyC,w eb egan by cloning the corresponding gene from A. orientalis and expressing it as ahexa-His fusion construct in E. coli (Figure 1b,T able S1 in the Supporting Information).…”
mentioning
confidence: 99%
See 2 more Smart Citations